Analysis of the Implementation of the Electronic Information and Transactions Law, as Revised, by the Indonesian National Police in North Sumatra - Sufrapto, Edi; Lubis, Zulkarnain; Siregar, Nina Siti Salmaniah (Universitas Medan Area, 2024)
Maintaining a balance between law enforcement and human rights in the implementation of the ITE Law is very important. The reform of the ITE Law is needed to ensure freedom of expression, and the right to privacy, and prevent the abuse of the law to silence criticism. This research focuses on the implementation of the ITE Law article by the Subdirectorate V of the North Sumatra Police. This research was conducted at the North Sumatra Regional Police, Medan, as a cybercrime surveillance center. Using a mixed methods approach, this study combines qualitative and quantitative data to understand the social reality in Sub-Directorate V Cyber Crime. These methods include interviews, documentation, observations, and literature studies. The development of the internet requires the government to update policies to overcome cyber challenges. The ITE Law faces issues such as rubber articles, threats to freedom of expression, legal uncertainty, digital security, and fair law enforcement. The revision is expected to create a fairer and more effective system.